ARSITEKTUR ENTERPRISE PADA BMKG DENGAN FRAMEWORK TOGAF ADM - Hartono, Henny; Meylovsky, Rourentsia; Andry, Johanes Fernandes (ISTEK WIDURI, 2020)
As a government institution that performs tasks in the fields of meteorology, climatology, air quality and geophysics, BMKG (Meteorology, Climatology and Geophysics Agency) does not yet have an integrated information system to support each of its activities, such as instrumentation, engineering and calibration, observation, processing, dissemination, and service. The purpose of this study is to produce enterprise architecture design including business architecture, data architecture, technology architecture, and application architecture, and produce activity solutions and information system solutions that can help BMKG in developing its business processes. In this study, the framework of enterprise architecture design uses The Open Group Framework (TOGAF) with the Architecture Development Method (ADM) method. The results of this study, namely a proposed TOGAF model that is tailored to the business needs process of BMKG in designing enterprise architecture for IS / IT development.